The ransom of the Jews : the story of the extraordinary secret bargain between Romania and Israel - Ioanid, Radu 1953- (Dee, 2005)
"After 1948, the 370,000 Jews of Romania who survived the Holocaust became one of the main sources of immigration for the new state of Israel. Almost all of them left their homeland to settle in Palestine and Israel. Behind Romania's decision to allow its Jews to leave were practical economic and political reasons: Israel paid for them, and Romania wanted influence in the Middle East. The trade satisfied both states and has remained a highly confidential matter - until now." "In The Ransom of the Jews, Radu Ioanid traces the extraordinary story of this secret exchange. Drawing upon restricted archival records and interviews with agents and others directly involved in the operation, he describes how Israel - not without second thoughts - traded cash, agricultural products, and sometimes political influence to bring Jews out of Romania. This privileged relationship between the two countries allowed Israel after 1967 to maintain in Bucharest its only embassy in the East European Communist bloc. It also permitted Nicolae Ceausescu, the anti-Semitic Romanian president, to emerge as a mediator in the Middle East peace process, in which he hoped to use Israel to improve his own relations with the United States."--BOOK JACKET.